Evaluation of Performance Assessment Based on Value for Money in Regional Genuine Revenue Agency in North Sulawesi Province - GAMPAMOLE, Ecclessia Evangelie; MORASA, Jenny; MARADESA, Djeini (PT Keberlanjutan Strategis Indonesia, 2024)
The Regional Revenue Agency of North Sulawesi Province is a public sector institution that has the duties and functions of carrying out the mandate of the community. As a Regional Government, public sector institutions must be responsible for carrying out their duties, one of which is in Financial Management. Value for money is one of the procedures for measuring the performance of public accountants to assess the Financial Management of the Regional Revenue Agency of North Sulawesi Province. This study aims to find out how the performance of Bapenda North Sulawesi Province in managing finances. This research is a descriptive qualitative research in which the data were obtained from interviews and Documentation. The results of the study show that the financial management of the North Sulawesi Province Bapenda is good because the finances of the North Sulawesi Province Bapenda are included in the criteria of Economical, Highly Efficient, and Very Effective even though in 2020 and 2021, the North Sulawesi Province Bapenda in carrying out the Realization of Local Own Revenue did not reach the Revenue Budget target Indigenous Area that has been targeted.